2022
DOI: 10.1007/s00464-022-09548-5
|View full text |Cite|
|
Sign up to set email alerts
|

Definition and reporting of lymphadenectomy and complete mesocolic excision for radical right colectomy: a systematic review

Abstract: Background Several procedures have been proposed to reduce the rates of recurrence in patients with right-sided colon cancer. Different procedures for a radical right colectomy (RRC), including extended D3 lymphadenectomy, complete mesocolic excision and central vascular ligation have been associated with survival benefits by some authors, but results are inconsistent. The aim of this study was to assess the variability in definition and reporting of RRC, which might be responsible for significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 134 publications
1
17
0
6
Order By: Relevance
“…Adequate patient selection, combined with an appropriate surgical procedure, is reported to result in a low risk of both early and late complications after surgery, when the postoperative recovery is prompt [26][27][28]. Timely detection and treatment of complications is also very relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate patient selection, combined with an appropriate surgical procedure, is reported to result in a low risk of both early and late complications after surgery, when the postoperative recovery is prompt [26][27][28]. Timely detection and treatment of complications is also very relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeries were performed following oncological principles if not contraindicated. Patients with right colon cancer were randomly assigned to complete a mesocolic excision as part of an undergoing study [ 20 ]. Peri-operative care followed the ERAS pathway, when applicable, for the whole study period [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review of 99 studies reporting the outcomes of radical colectomy for right colon tumours identified six different surgical techniques for which there were 35 unique definitions (Table 1). 8 The following manoeuvres were included in some or all of the different definitions:…”
Section: Terminologymentioning
confidence: 99%
“…Although Hohenberger's original description of CME for right colon tumours required a right medial visceral rotation (Cattell-Brasch manoeuvre), more recent descriptions of CME have been modified to more closely align with D3 lymphadenectomy (according to the definition of the Japanese Society for Cancer of the Colon and Rectum, JSCCR) where dissection is limited to the anterior aspect of the SMV and in some descriptions the SMA. 8,[11][12][13] CVL, which requires exposure of the SMA and SMV in order to ligate the ileocolic artery and vein at their origins, may or may not imply resection of the lymph nodes along the SMA and SMV. Unlike the imprecise Western CME literature, the JSCCR defines extent of lymphadenectomy for colon tumours according to anatomical lymph node groups as follows: D1: excision of paracolic lymph nodes along the marginal artery.…”
Section: Central Vascular Ligation and Extended Lymphadenectomymentioning
confidence: 99%
See 1 more Smart Citation